Promotion of women's mental health: the influence of physical health and the environment - Jacqueline de Souza; Jaqueline Lemos de Oliveira; Jordana Luiza Gouvêa de Oliveira; Letícia Yamawaka de Almeida; Loraine Vivian Gaino; Denise Marie Saint-Arnault
ABSTRACT Objective: To describe the results of a group of women's mental health promotion conducted by nurses. Method: This is a quantitative study of the pre- and post-test type. The participants were women aged between 20 and 64 years old attending a Primary Care Unit. We used the Sarason Social Support Questionnaire, the World Health Organization Quality of Life Assessment questionnaire, and the Rosenberg Self-Esteem Scale. Data were collected before, immediately after and three months after the intervention. Results: improvement in the physical and environmental quality of life was identified. However, there was no measurable change in the other indicators adopted. Conclusion: the ludic activities and the Body Mapping technique were promising for improving the physical and environmental domain of quality of life, constituting important tools for nursing care and interventions related to mental health in basic care.